Obstacles to Law Enforcement: The Use of Out-of-Court Resolutions in Domestic Violence and Abuse Cases in the United Kingdom - Eleanor, Amelia Jane (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
This research aims to examine the impact and effectiveness of the use of out-of-court resolution in cases of violence and domestic abuse in the UK and the implications for justice and victim protection. The research method uses a comprehensive literature review, varied data sources, and appropriate data collection and analysis techniques. This research involved the use of Freedom of Information Requests, interviews with experts, and qualitative and quantitative analysis to understand the use of out-of-court resolutions in cases of domestic violence and abuse in the UK. The result of this research is an in-depth study of the problem of domestic violence in the UK, which outlines the various forms of detrimental behavior that occur and the challenges faced in law enforcement. For example, Physical violence and emotional abuse are often interrelated, thus eroding the victim's self-confidence and leaving deep emotional wounds. By considering the concepts of restorative justice and community healing, this research highlights the complexity of handling domestic violence cases and the need for a thoughtful approach. Although there is healing potential in alternative approaches, criticism of their implementation emphasizes the need to consider the gender and power dynamics underlying violence.